Análisis de la percepción de violencia de género en mujeres de la comunidad California, cantón Rocafuerte - Romero García, Maikel Nicolás (2024)
Gender violence is a social pathology that affects the integrity of women, however, many of the victims consider this problem "normal" within the family circle and even think that it is a way of resolving conflicts. In addition, it is considered a violation of human rights. Therefore, the objective of this study was to analyze the perception of gender violence among women in the community of California, Rocafuerte canton. The research was developed from a quantitative, descriptive, non-experimental, cross-sectional approach. The method used was deductive. The survey technique was applied, which was based on the Gender Violence questionnaire of the Centro de Información Geoprospectiva (CIG), which measures psychological, physical, sexual, economic and patrimonial violence, where the inherent factors that lead to violence such as jealousy, control, discrimination and threatening behaviors are implicit. The study population consisted of 114 women, and a sample of 88 women was selected by simple random probability sampling. Women in early adulthood do perceive violence (76.7%), being of any kind of physical or psychological aggression, among others, while those in middle adulthood do not perceive any kind of violence, due to the naturalization of violent behaviors or events. It is evident that women do not perceive being abused by their partners, as they consider it normal; however, there is a significant percentage of women who do perceive gender-based violence.